Pengajaran Kosakata dalam Naskah Sulwān al-Nā’ī fī al-Fi‘l al-Wāwī wa-al-Yā’ī Karya Muḥammad al-Hajrusī - Nida Nurfazriah; Ade Kosasih; Ma’mun, Titin Nurhayati (Al-Ma‘rifah, 2019)
This research will explain about the text of Sulwān al-Nā’i Fī al-Fi‘l al-Wāwī wa-al-Yā’ī. The text of Sulwān al-Nā’i Fī al-Fi‘l al-Wāwī wa-al-Yā’ī was being found from the King Saud University online collection. The text was written by Muḥammad al-Hajrusī in 1300 H. While the research itself uses the analytic descriptive method, which the steps are related to its step on philology research, by then we can get the certain data from the object that being describe clearly. This Sulwān al-Nā’i Fī al-Fi‘l al-Wāwī wa-al-Yā’ī text is containing fi‘il (Arabic verbs) wāw and yā’ vocabularies which are well arrangement by their Hijā’īyah alphabet. The research shows that the text of Sulwān al-Nā’i Fī al-Fi‘l al-Wāwī wa-al-Yā’ī giving the information about 133 vocabularies of fi‘l and yā’. On its handwriting, Muhammad al-Hajrusī gave the example on the form of a sentence (kalimah mufidah). The writer hopes that the research will give many benefits to all communities and also can be a reference for a philology and linguistics discussion.